Evaluation of lead and chromium tolerance and accumulation level in Gomphrena Celosoides: a novel metal accumulator from lead acid battery waste contaminated site in Nigeria (2019)
Biology, tolerance, and metal (Pb and Cr) accumulating ability of Gomphrena celosoides were studied under hydroponic conditions. The seedlings were raised in Hoagland’s solution containing different concentrations of Pb (0, 500, 1000, 1500, 2000, 3000, 4000, and 5000mg l_1) and Cr (0, 50, 100, 150, 200, 300, and 400mg l_1). Biomass and metal accumulation in different plant parts were determined at seven (7) and fourteen (14) days after stress. Antioxidant enzyme activities, protein, and proline contents were estimated in stressed and unstressed plants. Gomphrena celosoides was able to tolerate Pb and Cr concentrations up to 4000 and 100mg l_1, respectively in hydroponic solution. Metal accumulation was concentration and duration dependent with the highest Pb (21,127.90 and 117,985.29mg kg_1) and Cr (3130.85 and 2428.90mg kg_1) in shoot and root, respectively found in the plants exposed to 5000mg l_1 Pb and 400mg l_1 Cr for 14 days. Proline, antioxidant enzyme activities, and protein contents were the highest in plant exposed to higher Pb and Cr concentrations for 7 and 14 days. Gomphrena celosoides could be considered as Pb and Cr accumulator with proline and increase in antioxidant enzyme activities being the tolerance mechanisms